Cooperative spectrum sensing method and performance analysis based on similarity between evidences - Zhiguo SUN; Xinyue REN; Zengmao CHEN; Ming DIAO (Tongxin xuebao)
The Dempster-Shafer(DS) evidence theory was applied to cooperative spectrum sensing and address the paradox of evidence in classical DS evidence theory, a new weighted distance measure based algorithm was proposed.Firstly, the evidences were extracted for each sensing user.Then, the weighted distance measure of extracted basic probability assignment data was adopted as the similarity between evidences of sensing users.Finally, the similarity of evidences was transformed into credibility, which was utilized as the weight to obtain the weighted average of basic probability assignment.In order to reduce the amount of data reported to the fusion center, the projection approximation method was employed to adjust the basic probability assignment.Both theoretical analysis and simulation results show that the proposed method can improve the detection performance of spectrum sensing while the paradox of evidence exists.Compared with traditional methods the cooperation overhead is reduced.